(untitled) (Journal of Population and Development, 2021)
The study tries to examine how the demographic changes has been occurred within the sub regions of the country by using selected indicators based on the existing data sheet of census 2011 and found Nepal has experienced very rapid demographic changes over the last three decades. The size and the density of the population have increased although the annual growth rate has been declined during a decade. As indicated by sex ratios there are more females than males in total population. The large volume of population are living in urban area (63%) and in province 3(21%) and small volume in province 6 (5.9%) though it is large state by an area. Since 1980 Nepal has seen significant declines in its total fertility rate and crude birth rate, crude death rate and infant mortality rate, alongside significant improvements taken place in life expectancy. This has resulted in noticeable changes in the age structure of the population in the country, the share in the population of children is shrinking against growing numbers and proportions older population aged 60 and above with large proportion of young working age population throughout the nation. This phase is also commonly known as the phase of youth bulge; demographic dividend’s or the window of opportunity and due to a higher percentage of young aged population, population momentum has been persistent. The window began in 1992 and projected to be up to 55 years. So it is the period for Nepal to utilize its young population in development.